2011
DOI: 10.1002/erv.1085
|View full text |Cite
|
Sign up to set email alerts
|

Becoming ‘whole’ again: A qualitative study of women's views of recovering from anorexia nervosa

Abstract: Objectives: The study explored women's perceptions of their recovery process and what recovery means to them in order to gain a better understanding of the predictors of recovery from anorexia nervosa (AN).Method: The data were analysed usingInterpretative Phenomenological Analysis (IPA). Semi-structured telephone interviews were carried out with fifteen women who received a diagnosis of AN and defined themselves as recovered/in recovery. The women were recruited from beat. Results:The women described their ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 35 publications
5
99
0
2
Order By: Relevance
“…It was found that, beyond the contribution of eating disorders characteristics and age, which, together, accounted for 16.2% of the variance, the QRI "Father Support" scale explained another 10.4% of the variance, meaning that the perceived availability of social support from the relationship with the father is positively associated with the motivation to recover. These results expand the findings of Jenkins and Ogden (2012), who found that in the eyes of recovered anorexics, social support from family members is an important part of the recovery process. "Pro-anorexia" websites, as previously described, are places in which females who are reluctant to seek treatment are being further reinforced with respect thereto, and are potentially drawn deeper into eating disorders.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It was found that, beyond the contribution of eating disorders characteristics and age, which, together, accounted for 16.2% of the variance, the QRI "Father Support" scale explained another 10.4% of the variance, meaning that the perceived availability of social support from the relationship with the father is positively associated with the motivation to recover. These results expand the findings of Jenkins and Ogden (2012), who found that in the eyes of recovered anorexics, social support from family members is an important part of the recovery process. "Pro-anorexia" websites, as previously described, are places in which females who are reluctant to seek treatment are being further reinforced with respect thereto, and are potentially drawn deeper into eating disorders.…”
Section: Discussionsupporting
confidence: 73%
“…Some studies have found evidence suggesting the importance of the patient's real and perceived relationships in the recovery process and outcome, though mostly via the patient's and therapist's perspectives. For example, Jenkins and Ogden (2012) analyzed interviews with recovered anorexics and found that women often commented on the value of support from family and friends as an important part of the recovery process. Drungaite (2009) studied autobiographies of anorexic patients who were either hospitalized or admitted to a day clinic, and found several themes that facilitated recovery, including "finding motivation to keep fighting towards recovery" and "the strengthening of the relationship between care giver and patient" ("care-giver" refers to clinic personnel).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, qualitative studies have reported that participants who have experienced AN think that being able to communicate their emotions and to develop supportive relationships are key aspects of recovery (Rance et al, 2015;Federici and Kaplan, 2008;Jenkins and Ogden, 2012;Kyriacou et al, 2009). Facial expressions of positive emotions, such as the smile, are essential for establishing rapport (TickleDegnen, 2006) and are related to cooperative intentions (Schmidt and Cohn, 2001), as well as social rewards (Shore and Heerey, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…No therapist she stated had ever told her about this.The tone adopted in this weblog is therefore one of dissatisfaction with therapy, suggesting that therapists can often contribute to establishing new disordered or obsessive behaviours even during the process of recovery. Partaking in therapy nevertheless supported recovery as it allowed individuals to recognise the extent of the damage they had done to their bodies (Jenkins and Ogden, 2012). However, where treatment had a focus on weight gain, female treatment seekers tend to express frustration and dissatisfaction (Kordy et al, 2002).…”
Section: Recognising the Consequences Of The Disorder (Anmentioning
confidence: 99%